2010
DOI: 10.3144/expresspolymlett.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silane treatment of carboxylic-functionalized multi-walled carbon nanotubes on the thermal properties of epoxy nanocomposites

Abstract: Abstract. The effect of silane treatment of carboxylic-functionalized multi-walled carbon nanotubes (COOH-MWCNTs) on the thermal properties of COOH-MWCNTs/epoxy nanocomposites was studied by comparing the research results on differential scanning calorimetry and thermogravimetric analysis data of silane treated COOH-MWCNTs/epoxy system with those of as-received COOH-MWCNTs/epoxy system. At the initial curing stage, silane treatment of COOH-MWCNTs does not change the autocatalytic cure reaction mechanism of COO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
4
18
0
Order By: Relevance
“…DSC is often used to study the effect of nanofillers on the cure behaviors of epoxy resin [11,16,[25][26][27]. In present work, dynamic kinetic studies based on Kissinger and Flynn-Wall-Ozawa (FWO) models [26][27][28] were utilized to investigate the DGEBA/ CTBN/MWCNT-COOHs nanocomposites.…”
Section: Cure Behaviorsmentioning
confidence: 99%
“…DSC is often used to study the effect of nanofillers on the cure behaviors of epoxy resin [11,16,[25][26][27]. In present work, dynamic kinetic studies based on Kissinger and Flynn-Wall-Ozawa (FWO) models [26][27][28] were utilized to investigate the DGEBA/ CTBN/MWCNT-COOHs nanocomposites.…”
Section: Cure Behaviorsmentioning
confidence: 99%
“…Before stored in desiccators, COOH-MWCNTs were dried at 110°C for 24 h in vacuum to eliminate the agglomeration caused by hygroscopic absorption, as well as removing planar water, which would hinder the interaction between coupling agent and COOH-MWCNTs. Micrographs of the rod-shaped COOH-MWCNTs and the COOH-MWCNT/epoxy composite can be seen in our previous work [31]. The starting material for GNPs was graphite intercalation compound (GIC) particles (500 µm), i.e.…”
Section: Experimental 21 Materialsmentioning
confidence: 99%
“…They reported that MWCNTs had an accelerating effect in the initial curing stage, whereas in the later curing stage, MWCNTs prevented from the occurrence of vitrification [20]. However, carboxylic functionalization of MWCNTs did not change the autocatalytic cure reaction mechanism of epoxy nanocomposites and had catalytic effect on the curing process [21,22]. Jana and Zhong [23] found that expanded graphite (EG) did not significantly impede the cure reaction of epoxy.…”
mentioning
confidence: 99%
“…Differential scanning calorimetry (DSC) may be considered as one of the most interesting techniques for kinetic analysis of cure reactions of thermosetting systems [13][14][15]. Numerous studies on cure kinetics of epoxy in presence of carbon-based nanofillers have been investigated [16][17][18][19][20][21][22][23][24][25]. Recently, Allaoui and El Bounia [16] had reviewed the influence of CNTs on the cure kinetics of epoxy resin.…”
mentioning
confidence: 99%
See 1 more Smart Citation